Modelo para el soporte documental de sistemas de gestión de la calidad en la plataforma de Software Eclipse Process Framework Composer (2017)
In the present project of degree is designed a model that allows the construction of documental platforms for the Systems of Management of the Quality (QMS), using the software Eclipse Process Framework Composer (EPFComposer). For this, a working methodology is developed in which the normative framework is studied in relation to the documentary requirements established in the norms ISO and the implementation of the software of design for the construction of interactive documentary structures for the systems of management of the quality. Complementary to this, it should be noted that the construction of the model takes into account a real documentary structure of a Quality Management System by the organization.